(untitled) (International Educators Conference, 2025)
The interest policy of the Central Bank is an important part of the state’s economic policy and plays an important role in the social and economic growth of the state. It is based on the separation of tactical and strategic tasks in the reform of monetary instruments and methods. The strategic task is to start using generally accepted means of monetary control, which are specific to countries with developed market economies.